MENINGKATKAN TATA KELOLA DAN DIGITALISASI PENYELENGGARAAN PEMERINTAHAN MENGGUNAKAN PRINSIP GOOD GOVERNANCE DI KABUPATEN JEMBER - Saputri, Maharani Dwi Saputri (Kybernology Jurnal Ilmu Pemerintahan dan Administrasi Publik, 2025)
This research aims to analyze the role of digitalization in improving government governance in Indonesia. Government digitalization is expected to increase efficiency, transparency and accountability in the management of public administration. The research method used is descriptive qualitative data analysis, by exploring information from related literature and government policies that focus on digital transformation. The data collected was analyzed thematically to see how the application of digital technology has influenced government bureaucratic structures and processes. The research results show that government digitalization can speed up the public service process, reduce corruption, and increase public access to public information. However, challenges in implementation, such as the digital divide between regions and limited skilled human resources, remain obstacles that need to be overcome. The implication of this research is the importance of careful planning and capacity development in implementing digitalization in order to realize better governance that is responsive to community needs.